Weight Reduction in Chili Pepper Sale Transactions: An Analysis of ‘Urf and the Parties’ Mutual Consent from the Perspective of Islamic Commercial Jurisprudence - Diyah Sulistiowati; Ninda Herlina Rahmawati (Yayasan Azhar Amanaa Yogyakarta, 2026)
Weight reduction in chili pepper sale transactions has become a customary practice in Temanggung, Indonesia. It is conducted transparently based on the quality and condition of the produce, including defects, impurities, and potential weight loss. While generally accepted as ‘urf and based on mutual agreement, a small number of sellers do not fully consent to the reduction, raising questions about the role of ‘urf and mutual consent (tarāḍin) in Islamic commercial transactions. This study examines the practice and its conformity with fiqh muʿāmalah using a qualitative case study approach based on field observations and interviews. The findings show that weight reduction is an established and socially accepted practice and may be recognized as ‘urf because it is repeatedly practiced and collectively acknowledged. From the perspective of fiqh muʿāmalah, the practice is permissible when conducted transparently, agreed upon, and free from deception or injustice (ẓulm). However, ‘urf alone does not legitimize the practice where mutual consent is absent. Thus, the practice is consistent with fiqh muʿāmalah only when transparency, agreement, and genuine mutual consent are ensured